If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4k + 3 = -5k + 21 Reorder the terms: 3 + 4k = -5k + 21 Reorder the terms: 3 + 4k = 21 + -5k Solving 3 + 4k = 21 + -5k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '5k' to each side of the equation. 3 + 4k + 5k = 21 + -5k + 5k Combine like terms: 4k + 5k = 9k 3 + 9k = 21 + -5k + 5k Combine like terms: -5k + 5k = 0 3 + 9k = 21 + 0 3 + 9k = 21 Add '-3' to each side of the equation. 3 + -3 + 9k = 21 + -3 Combine like terms: 3 + -3 = 0 0 + 9k = 21 + -3 9k = 21 + -3 Combine like terms: 21 + -3 = 18 9k = 18 Divide each side by '9'. k = 2 Simplifying k = 2
| 3y+2=1+2y | | 4x+1.4=3x+1.3 | | 5x-2=4-x | | 9x-2=2x-30 | | 6-5y=4y+15 | | 26x+96=16x-41 | | 12w-30=7w+19 | | 12x-28=28x-20 | | 16x^2-12x-7=0 | | -8x^2+3x+3=0 | | 5p+7=4p-1 | | 5(x-5)=3x-11 | | 12m+3=10m+16 | | 6y-5=y-20 | | 3x-10=5x+1 | | 3(4m+1)=2(5m+4) | | 6x-6=11x-11 | | 25-2(4x+2)=7x-6(4x-2) | | 3x-(2x+5)=12+5(x-1) | | 3x-(2x+5)=12+5(x+1) | | 4(2d-7)=32 | | 4y-6=2y-5 | | 3a-a=b+c | | 3x+5y-67=3 | | 2x^2-11=85 | | 3a=(a-b)+c | | 5(m-1)=2(2m+6) | | 4(4x-1)-2=-3x+3(2x-7) | | 13x=-15 | | 8+9a=20-3a | | 15x-1=7x-17 | | -5(x-7)=4(x+4)-8 |